THE QUALITY OF BALI LOCAL PORK REVIEWING FROM OBJECTIVE TESTS - Putra, Putu Aditya Pratama Arta; Tenaya, I Wayan Masa; Mufa, Romy Muhammad Dary; Swacita, Ida Bagus Ngurah (Buletin Veteriner Udayana; Vol. 15 No. 4 August 2023DO - 10.24843/bulvet.2023.v15.i04.p01, 2023)
The availability of safe, healthy and whole animal food is a concrete manifestation of one of the development goals in the field of food security. One of the foodstuffs of animal origin that contains high nutritional value is pork. The purpose of this study was to determine the quality of local Balinese pork when viewed from an objective test. Evaluation of meat quality and health is carried out objectively. Objective assessment is carried out with the help of laboratory equipment or with comparison standards. objective assessment includes an assessment of pH, water holding capacity and water content. The samples used were Balinese pork as many as 12 samples per each test. Data on pH, water content, and water holding capacity were analyzed by the Variety Print Test. The results showed that the objective tests of Balinese pork slaughtered at the traditional slaughterhouse of Penatih Village, Denpasar from four different muscle locations (fore legs, neck, hind legs, and abdomen) showed good results. not significantly different. The average in each test shows good results and is good for consumption when compared to other breeds of pigs.